Organizational innovativeness scale: Evidence of validation for the Brazilian context - Silva, Renata Gonçalves Santos; Broilo, Patrícia Liebesny; Frio, Ricardo Saraiva; Sampaio, Claudio Hoffmann; Perin, Marcelo Gattermann (Revista de Administração da UFSM, 2018)
Against the overlap of concepts and measurements regarding organizational innovativeness, Ruvio et al. (2014) present a multidimensional definition of the construct and validate a scale for its operationalization. The present study aimed to validate this scale in the Brazilian context. Additionally, focusing the construct nomological validity, the study aimed to empirically verify the relationship between organizational innovativeness on its five dimensions and the level of innovation of the organization. A survey was conducted with participation of 165 executives of organizations from various sectors. The results validate the scale for usage in the Brazilian context and indicate that organizational innovativennes is as a predictive variable of the degree of innovation, which tends to impact firms performance in the long run.